Work Demands and Cognitive Health Inequities by Race and Ethnicity: A Scoping Review. (19th February 2022) - Gonzales, Ernest; Whetung, Cliff; Lee, Yeonjung Jane; Kruchten, Rachel
Abstract: Background and Objectives: This scoping review aimed to chart the scientific literature on the association between workplace demands with cognitive health, and whether race and ethnicity have a direct or indirect relationship between occupational complexity and cognitive health. Research Design and Methods: PRISMA scoping review guided this study. Peer-reviewed articles were drawn from 5 databases. Inclusion criteria were populations aged 18 and older, U.S.-based studies, a comprehensive conceptualization of workplace demands, and cognitive health outcomes. All articles were screened by title and abstract; qualifying articles proceeded to full-text review. Results: The majority of studies drew from theories that did not interrogate heterogeneity and minority aging experiences. Consequently, the majority of studies did not include race and ethnicity in their analyses. A small and growing body of research drew from critical perspectives and interrogated cognitive health inequities by race and ethnicity within the context of workplace demands. The association between workplace demands and cognitive health is not linear when race and ethnicity are examined. Emerging evidence suggests interventions to improve substantive complexity among racial and ethnic minorities, and individuals with low education are a promising avenue for intervention research. Discussion and Implications: We discuss integrating emerging theories, such as minority stress and revised social determinants of health frameworks, to sharpen the focus and broaden our understanding on racial and ethnic cognitive health inequities in an emerging area of prevention research. This research can advance our basic understanding of preventable health inequities as well as provide important information for interventions.